Collaborative and Social Learning using Virtual Worlds: Preparing Students for Virtually Anything - Erenli, Kai; Ortner, Gerhard (International Journal of Advanced Corporate Learning (iJAC), 2011)
"Teams, increasingly more than individuals, are charged with the most challenging and mission-critical projects. Leaders need to evaluate and motivate from a distance. And the makeup of teams is increasingly complex â?? they´re bigger, more diverse, more geographically distributed, composed more of specialists than generalists, and much more dependent on technology than in the past. And difficult economic times only accent these challenges." This statement made by Reeves and Read in their Book â??Total Engagement